TERMS OF PROVISION OF SAFE OPERATION OF TOWING VEHICLES OF COMMERCIAL AVIATION AIRLINES - Кулик, М. С.; Купчик, М. В. (Proceedings of National Aviation University (archive), 2020)
The analysis of dynamics of growth of the world park of planes with various types of the power plant, in particular with turbo propellers, is given. Particular attention is paid to the aviation park of Russia and Ukraine. The problems of the further exploitation of aircraft with turbopropeller engines are considered